Kreyol Intertextuality and Decolonizing Narrative in Veillées noires - Meehan, Kevin (Dalhousie French Studies)

(untitled) (Department of French, Dalhousie University, 2020)
This essay identifies three levels of intertextuality in the short story, “Echec et mat” by Léon-Gontran Damas. Incorporating folkloric tales, lyrics from popular music, and 19th Century satiric writing in Kreyol, “Echec et mat” offers a microcosm of the intertextual techniques employed throughout the entire collection, Veillées noires. In particular, I analyze Damas’s embedding of a satire written and published in Kreyol by Guadeloupean author Paul Baudot. While this Kreyol satire—written by a white béké author from the mid-19th Century—is ambiguous politically, and must be determined by musical and folkloric references, Damas nevertheless signals the importance of earlier Caribbean writing in Kreyol. Such writing co-exists with other forms of cultural production and is part of the reservoir from which Damas draws to assemble his complex anti-colonial discourse. These intertextual traces reveal a cultural identity that is plural as well as anti-colonial.